Diameter stem growth and phenology of Tabebuia Rosea (Bertol.) DC. in Costa Grande, Guerrero, Mexico - Pineda-Herrera, Elizandro; Valdez-Hernández, Juan Ignacio; Pérez-Olvera, Carmen De la Paz (Acta Universitaria, 2016)
Tabebuia rosea is a multipurpose tree species whose rate of growth and phenology have been studied in a few tropical forest of Mexico, beingthis information for knowledge, conservation and management helpful. In this work, carried out for 17 months in Zihuatanejo de Azueta, Guerrero, growth was measured every two months and compared between diametric categories and qualities-positions crown. Also bimonthly four phenological events (leaf falling, flowering, fruiting, leaf flushing) were recorded and correlated with precipitation and temperature. Average annual growth was 0.58 cm and its curve fitted to logistic model. Leaf flushing was correlated to precipitation (p < 0.05). Growth rate was not related to trees size or crown position, a positive association was found between seasonal pattern of rainfall, annual increments and leaf flushing.
Keywords: Array; Array; Array; Array